Using KBase to Assemble and Annotate Prokaryotic Genomes. Issue 1 (15th August 2017) - Allen, Benjamin; Drake, Meghan; Harris, Nomi; Sullivan, Tarah
Abstract: The DOE Systems Biology Knowledgebase (KBase, http://kbase.us/ ) is an open‐access bioinformatics software and data platform for analyzing plants, microbes, and their communities. KBase enables scientists to create, execute, collaborate on, and share reproducible analyses of their biological data in the context of public data and private collaborator data. For microbiologists researching prokaryotes, KBase offers analysis tools for performing quality control and assessment of Next‐Generation Sequencing reads, de novo assembly, genome annotation, and tools for analyzing structural and functional features of genomes. This unit demonstrates an example workflow for taking a comparative and iterative approach to assembly and annotation of prokaryotic genomes using KBase that can be used by microbiologists seeking to perform isolate analysis in a rapid and reproducible fashion. © 2017 by John Wiley & Sons, Inc.